PERANCANGAN PONDASI TIANG PANCANG DERMAGA PACKING PLANT BANJARMASIN – KALIMANTAN SELATAN - Mandala Siliwangi; Ferry Rizki Pratomo; Sri Prabandiyani R.W.; Siti Hardiyati (Jurnal Karya Teknik Sipil, 2014)
The construction project of Packing Plant Jetty located in the Banjarmasin, South Kalimantan. This jetty construction is intended as a means to distribute  goods in bulk through the sea using ships. In general, this building using jetty type. The purpose of this thesis are to design jetty sub-structure, in this case is jetty pile foundation on buildings of jetty, among others are : Berthing Dolphin, Mooring Dolphin, Catwalk and Trestle. From the several load possible  that will occur in the structure, it is necessary to do an analysis of the bearing capacity of soil and pile. The method used to analyze the pile bearing capacity of the vertical load is a method of Meyerhof, whereas for the analysis of the bearing capacity of soil and pile to lateral forces used Broms method. For the bearing capacity of the pullout forces used Sowa method. Based on the analysis performed, piles that used are concrete spun pile with pile length 37 m and diameters 80 cm for Berthing Dolphin and Mooring Dolphin with the configuration for each buildings in a row are 9 and 4 piles with axial bearing capacity 578,671 ton and 151,799, lateral load capacity 15,006 ton and 10,774 ton, pullout capacity 1383,696 ton and 527,976 ton. Catwalk  and Trestle using piles with a diameter of 40 cm . Those axial bearing capacity are 67,373 ton and 71,308 ton, lateral load capacity are 0,802 ton and 1,277 ton. The settlement for single piles at Dolphin Berthing, Mooring Dolphin, Catwalk and Trestle are 3,224 mm, 0.8454 mm, 0552 mm and 0552 mm, The settlement for the group piles Berthing Dolphin and Mooring Dolphin are 7,897 mm and 1,577 mm.